Kinetics of hyaluronic acid production by streptococcus zooepidemicus / Mashitah, M.D and Fazliani, N.S - M.D, Mashitah; N.S, Fazliani (2008)
Kinetic studies of hyaluronic acid (HA) production by Streptococcus zooepidemicus were performed in an aerobic fermentation. An unstructured model taking into accounts the cell growth and HA production is proposed. It was found that the logistic model incorporated by Leudeking Piret model described fairly well the experimental observations compared to Monod model. The model however is influence by the glucose limitation and by-product inhibition.